Clinical Validation of R-T Estimation for CoaguChek XS INR Results. (August 2016) - Richter, Christopher; Taylor, James; Wright, Joyanna; Fletcher, Bradley
Background: Despite the emergence of several new oral anticoagulants, warfarin remains a widely used form of anticoagulation that continues to have a role in the treatment of cardiac and thrombotic conditions.Objective: The goal of this study was to evaluate whether the R-T estimation, an equation developed in a previous study, was a valid clinical tool in managing patients' warfarin therapy in an anticoagulation clinic in lieu of obtaining a venipuncture international normalized ratio (INR) secondary to a high CoaguChek XS (CXS) INR.Methods: This study used a randomized double-blind method to compare the clinical decisions made using venipuncture or CXS machine and recorded the INR, percentage dose change, time to clinical decision from check-in, and scheduled follow-up.Results: In the analysis of the difference in percentage dose change, a 1.0% (95% CI = −0.78 to 2.68; P = 0.27) difference was observed overall, and a 1.2% (95% CI = −0.59 to 2.95; P = 0.18) difference was observed in the 4 to 5.9 subgroup. Clinical decisions were reached 17 minutes faster (95% CI = 11-24; P < 0.001) overall and 17 minutes faster (95% CI = 10-24; P < 0.001) in the 4 to 5.9 subgroup. Scheduled follow-up was 0.38 weeks sooner (95% CI = 0.01-0.67; P = 0.014) overall and 0.36 weeks sooner (95% CI = 0-0.66; P = 0.041) in the 4 to 5.9 subgroup.Conclusions: The results of this study support the use of the R-T estimation for correction of INR values obtained using the CXS meter when the INR is in the range of 4 to 5.9. This correction will allow clinics using this device to more efficiently manage patients taking warfarin.